2011
DOI: 10.3345/kjp.2011.54.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for respiratory system impedance using impulse oscillometry in healthy preschool children

Abstract: PurposeThe normal values for lung resistance and lung capacity of children, as determined by impulse oscillometry (IOS), are different for children of different ethnicities. However, reference values there is no available reference value for Korean preschool children have yet to be determined. The aim of the present study was to determine the normal ranges of IOS parameters in Korean preschool children.MethodsA total of 133 healthy Korean preschool children were selected from 639 children (aged 3 to 6 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
5
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 28 publications
8
66
5
2
Order By: Relevance
“…As occurs with other pulmonary function tests, we found that IOS values progressively changed as children grew up. In many of the published IOS reference equations, such as those proposed by Park et al, 12 Lee et al, 13 Hellinckx et al, 14 and Frei et al, 15 the relationship between IOS variables and anthropometric parameters such as height was found to follow a straight-line fitting. This is in contrast with our results, in which a curvilinear fitting was observed, and might be explained by the narrower age range studied by these authors (up to the age of 10 y).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As occurs with other pulmonary function tests, we found that IOS values progressively changed as children grew up. In many of the published IOS reference equations, such as those proposed by Park et al, 12 Lee et al, 13 Hellinckx et al, 14 and Frei et al, 15 the relationship between IOS variables and anthropometric parameters such as height was found to follow a straight-line fitting. This is in contrast with our results, in which a curvilinear fitting was observed, and might be explained by the narrower age range studied by these authors (up to the age of 10 y).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that subtle differences existed in several IOS variables between males and females; thus, the sets of reference values were calculated separately for each gender. In previous studies, Park et al 12 and Nowowiesjka et al 17 also presented reference values for boys and girls separately, although no mention was made concerning how large or how close to statistical significance those differences were. In our study, this slight gender difference was more noticeable in older subjects in the case of respiratory resistances, and in the younger population for respiratory reactances (as observed in the supplementary materials at http://www.rcjournal.com).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, salivary SP-D concentrations correlated positively with the percentage Abbreviations: ALX, area of low reactance; Fres, resonant frequency; R5 and R20, airway resistance at 5 Hz and 20 Hz; X5, reactance at 5 Hz. neither gender nor race appears to be an important covariate [10,11,13]. In this study, age had the largest absolute b value among the independent variables of the regression equations, indicating that it was the most influential predictive variable of almost all FOT indexes.…”
Section: Salivary Sp-d Levels Correlate With R5-r20 In Asthmatic Chilmentioning
confidence: 89%
“…FOT has been shown to be more sensitive than spirometry in identifying disturbances of peripheral airway function and has been successfully used for the assessment of pulmonary function in children who cannot perform spirometry during asthma attacks [7][8][9]. However, various factors, including age, sex, height, and weight, are known to influence FOT parameters [10][11][12][13]. Therefore, standardization of FOT indexes with reference values is essential for accurate data acquisition.…”
Section: Introductionmentioning
confidence: 99%